Polymer composites,volume 1: macro- and microcomposites - Thomas, Sabu (Wiley-VCH, 2012)
Polymer composites are materials in which the matrix polymer is reinforced with organic/inorganic fillers of a definite size and shape, leading to enhanced performance of the resultant composite. These materials find a wide number of applications in such diverse fields as geotextiles, building, electronics, medical, packaging, and automobiles